2010
DOI: 10.1007/s00259-010-1416-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of FDG PET/CT in the diagnosis of suspected recurrent ovarian cancer: is there an impact of FDG PET/CT on patient management?

Abstract: Our results confirm that FDG PET/CT is a superior posttherapy surveillance modality for the detection of recurrent ovarian cancer than diagnostic CT imaging. Furthermore, integrated FDG PET/CT was useful specifically in optimizing the treatment plan and it might play an important role in treatment stratification in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
17
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 40 publications
8
17
0
3
Order By: Relevance
“…In accordance with our results, we found that the inclusion of PET/CT in the management of patients with recurrent ovary cancer had an impact on the decision making in 42% of subjects. As reported in the literature, the change in management of patients with OC who have undergone FDG PET/ CT ranges between 25% and 58% (10,(15)(16)(17)(18). OC can disseminate to the peritoneum.…”
Section: Discussionmentioning
confidence: 97%
“…In accordance with our results, we found that the inclusion of PET/CT in the management of patients with recurrent ovary cancer had an impact on the decision making in 42% of subjects. As reported in the literature, the change in management of patients with OC who have undergone FDG PET/ CT ranges between 25% and 58% (10,(15)(16)(17)(18). OC can disseminate to the peritoneum.…”
Section: Discussionmentioning
confidence: 97%
“…Generally, the diagnostic performance indices of combined PET/CT come in line with those reported in literature. (24)(25)(26)(27) However, the sensitivity of Ce-CT is generally higher than others reported in literature. (24, 25, 28, 29) .…”
Section: Discussionmentioning
confidence: 84%
“…Lors de la suspicion de récidive (devant une élévation du marqueur CA 125 ou des signes cliniques d'appel), elle a démontré une valeur diagnostique satisfaisante et même meilleure que les méthodes d'imagerie conventionnelle dans cette indication [6][7][8][9]. Dans une cohorte prospective de 90 patientes, on a ainsi pu observer un impact sur la prise en charge des patientes dans 60 % des cas [10].…”
Section: Introductionunclassified